Characteristic Analysis Of Arc Flash In Low Voltage Electrical Power Caused By The Effect Of Short Circuit Impedance - Asfani, Dimas Anton; Negara, I Made Yulistya; Fahmi, Daniar; Hernanda, I.G.N Satriyadi; Irmawati, Novia Ayu (JAVA Journal of Electrical and Electronics Engineering, 2016)
Fire cases caused by an electrical short circuit (arc flash) at low voltage are still very high in Indonesia recently. Several studies about characteristic analysis of arc flash at low voltage has been done. In this study, an experiments of arc flash phenomena at low voltages using an artificial short-circuit device is conducted.  The arc flash’s experiment is applied to low voltage stranded conductor cable 1.5mm2 (24 filaments) with resistive load using some objects as short-circuit media (metallic objects, non-metallic objects, and solution).  Low voltage arc flash characteristics such as maximum current, maximum power, duration and energy of each short circuit media to be analyzed. The results of this study is expected to design protective device (detector) that can be detected low voltage arc flash in future research